2011
DOI: 10.1016/j.yexmp.2011.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Small molecule inhibitors of the host cell COX/AREG/EGFR/ERK pathway attenuate cytomegalovirus-induced pathogenesis

Abstract: As with other herpesviruses, human cytomegalovirus (hCMV) has the ability to establish lifelong persistence and latent infection following primary exposure, salivary glands (SMGs) being the primary site of both. In the immunocompromised patient, hCMV is a common cause of opportunistic infections, and subsequent morbidity and mortality. Elucidating the molecular pathogenesis of CMV-induced disease is critical to the development of more effective and safer drug therapies. In the present study, we used a novel mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 49 publications
3
29
0
Order By: Relevance
“…That human SG-MEC is a virally implicated pathology, is further supported by our finding that purified mouse CMV (mCMV) induces cellular pathology in an in vitro mouse SG organ model that displays a number of histologic and molecular characteristics similar to human MEC Melnick et al, 2011). Specifically, we have demonstrated that mCMV induces (1) mesenchymal-to-epithelial transformation (MET); (2) epithelial and mesenchymal hyperplasia, dysplasia and neoplasia; (3) loss of basement membrane zone components, reduced expression of epithelial-specific adherens junction proteins (E-cadherin, p120), and admixing of stromal-derived and epithelial-derived cells; (4) expression of CRTC1 protein, a protein found in SG MECs but not in normal SG tissue (Tirado et al, 2007); and (5) upregulation of the activated COX/AREG/EGFR/ERK signaling pathway.…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…That human SG-MEC is a virally implicated pathology, is further supported by our finding that purified mouse CMV (mCMV) induces cellular pathology in an in vitro mouse SG organ model that displays a number of histologic and molecular characteristics similar to human MEC Melnick et al, 2011). Specifically, we have demonstrated that mCMV induces (1) mesenchymal-to-epithelial transformation (MET); (2) epithelial and mesenchymal hyperplasia, dysplasia and neoplasia; (3) loss of basement membrane zone components, reduced expression of epithelial-specific adherens junction proteins (E-cadherin, p120), and admixing of stromal-derived and epithelial-derived cells; (4) expression of CRTC1 protein, a protein found in SG MECs but not in normal SG tissue (Tirado et al, 2007); and (5) upregulation of the activated COX/AREG/EGFR/ERK signaling pathway.…”
Section: Introductionmentioning
confidence: 55%
“…Despite the well-documented overexpression of the EGFR → ERK signaling pathway in MEC (Akrish et al, 2009;Ito et al, 2009;Lujan et al, 2010), there has been limited to no success with inhibition of this pathway (Bell and Hanna, 2012;Gillespie et al, 2012), not unlike that seen with other malignancies (Engelman and Settleman, 2008). Using our previously described mouse model of CMV-induced SG dysplasia/neoplasia Melnick et al, 2011), we provide evidence that concurrent inhibition of ERK phosphorylation and inhibition of CMV replication obviates progressive pathogenesis and results in complete SG rescue (regression). These findings provide a mechanistic foundation for clinical trials that utilize similar concurrent treatment with extant FDA-approved drugs.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…A different activity of HCMV in seropositive patients may be the explanation for the contradicting results in clinical trials, comparing seropositivity of individuals with the occurrence of restenosis or atherosclerosis. Recently Melnick et al, [30] suggested that upregulation of ERK phosphorylation is necessary for initial HCMV induced pathogenesis. The presented models are suitable for further studies on stimulatory and inhibitory effects of HCMV-infection in human coronary cells.…”
Section: Discussionmentioning
confidence: 99%
“…This exemplifies a sophisticated approach that poxviruses employ to differentially manipulate EGFR-triggered events for their benefit. Proper EGFR signal transduction is critical for the entry of several virus types into cells (14,36), and aberrant EGFR expression or signaling is associated with certain types of cancers (39). Thus, identifying how VACV modulates EGFR-mediated signal transduction pathways could likely yield new approaches and targets for antiviral or anticancer therapies.…”
Section: Discussionmentioning
confidence: 99%